2015
DOI: 10.1002/ece3.1560
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects on egg production and level of paternity in a natural population of a simultaneous hermaphrodite snail

Abstract: In a seasonal environment, the suitable time window for females to reproduce is restricted by both environmental conditions and the availability of males. In simultaneous hermaphrodites, which are female and male at the same time, selection on a trait that is solely beneficial for one sexual function cannot occur independently. Therefore, it is assumed that the optimal time window for reproduction is a compromise between the two sexual functions in simultaneous hermaphrodites, mediated by environmental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Only a few studies have examined temporal trends in multiple paternity in hermaphrodites, all of them using laboratory‐laid egg clutches. Neither in the marine snail Aplysia californica (Angeloni et al., ) nor in A. arbustorum (Janssen & Baur, ), there was any evidence for such trends, although in A. arbustorum one study found more multiple paternity among adult than subadult snails (Kupfernagel & Baur, ). Also in gonochorists, data on within‐season variation in multiple paternity are very scarce.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Only a few studies have examined temporal trends in multiple paternity in hermaphrodites, all of them using laboratory‐laid egg clutches. Neither in the marine snail Aplysia californica (Angeloni et al., ) nor in A. arbustorum (Janssen & Baur, ), there was any evidence for such trends, although in A. arbustorum one study found more multiple paternity among adult than subadult snails (Kupfernagel & Baur, ). Also in gonochorists, data on within‐season variation in multiple paternity are very scarce.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in the freshwater snail Lymnaea stagnalis, 59% of clutches were multiply sired and clutches had a minimum number of 1.8 fathers on average (Nakadera et al., ). In Physa acuta , another freshwater snail, clutches had a mean of 3.8 fathers (Henry et al., ), and in the terrestrial snail Ariana arbustorum 68.3% to 100% of clutches were multiply sired, and clutches had 4.0–6.1 fathers on average (Janssen & Baur, ; Kupfernagel & Baur, ; Kupfernagel et al., ). Interestingly, our estimates of multiple paternity rates are approximately in the same range as these laboratory‐based estimates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations